The Effect of City Waste Giving With Various Concentrations on Growth and Results Red Lettage Plants - Devi Andriani Luta; Armaniar Armaniar (Budapest International Research and Critics University, 2021)
The research was conducted at the Development University of Pancabudi, the agricultural lab of Glugur Rimbun starting from January until April 2020. This research was conducted using an experimental method using a Randomized Block Design (RAK) with 4 treatments and 6 groups/replication. The observed plant response was in the form of a plant height variable (cm), several leaves (strands), wet weight of plants (g), dry weight of plants (g), root length (cm), and organoleptic test. Based on the research results obtained, then it can be concluded that hydroponic nutrition with a concentration of 450 ppm (P1) has a good effect on the growth of red lettuce plants, namely producing high18.64 cm at the 4th week and the number of leaves 21.80 at the 4th week, weight 114.22 g in wet, 5.94 in dry, and 29.18 cm in root length.